The Effect of The Number of Reference Points and Distribution on Coordinate Transformation in Underground Mining Measurements - Tasçı, Levent; Arslan, Hacı Sait (My University, 2023)
This article focuses on examining the effect of the number and distribution of reference points on coordinate transformations in underground mining measurements using a handheld laser scanner. The points inside the mine were measured as reference using a Total Station. The same point cloud data was subjected to coordinate transformation with different numbers and elevations of reference points. It was observed that the homogeneous distribution of reference points used in the transformation increases precision in the horizontal and vertical directions. Both homogeneous and excessive use of transformation points result in the same good results in the horizontal, but in the vertical, it improves further. Using a large number of transformation points and using them at different elevations results in the same good results in the horizontal, but in the vertical, it increases precision even more. The article concludes that a sufficient number of homogeneously and heterogeneously distributed reference points are necessary for accurate coordinate transformation.
Keywords: Point Cloud; Laser Scanner; 3D Transformation; Geodetic Coordinate